Experimental Study on Super-cooling Degree of Nanofluids for Cryogenic Cool Storage - He Qinbo; Tong Mingwei; Liu Yudong (Zhileng xuebao)
Four different concentration TiO2-BaCl2-H2O nanofluids with 20nm TiO2 were prepared by supersonic oscillator through adding hydrophilic dispersant into BaCl2 solution. BaCl2-H2O and TiO2-BaCl2-H2O nanofluids were tested experimentally. The results show that nanofluids have remarkably lower supercooling degree than BaCl2-H2O, and the beginning nucleation time of nanofluids is ahead of BaCl2-H2O. Moreover, their crystallization time is lower than that of BaCl2-H2O. Also, the crystallization mechanism was analyzed for the influence of the nano TiQ2 particles on BaCl2-H2O.